The moderating roles of intrinsic and extrinsic religiosity on the relationship between social networks and flourishing: a study on community-dwelling widowed older adults in Malaysia - Hui, Foh Foong; Hamid, Tengku Aizan; Ibrahim, Rahimah; Bagat, Mohamad Fazdillah (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Widowhood affects the social networks and well-being of older adults. Religion might moderate the relationship between a stressor and well-being. This study aimed to identify the moderating roles of intrinsic and extrinsic religiosity on the relationship between social networks and flourishing among widowed older people and whether this relationship varied across gender. This study involved 655 community-dwelling widowed older Malaysians from Wave 1 (2012–2013) of “Identifying Psychosocial Risks and Quantifying the Economic Costs of Age-Related Cognitive Decline among Older Malaysians” in Peninsula Malaysia. The moderated hierarchical multiple linear regression analysis was conducted to examine the moderating roles of religiosity. Results showed that the moderating effect of religiosity on the relationship between social networks and flourishing was only observed for extrinsic religiosity, not intrinsic religiosity. In terms of gender differences, extrinsic religiosity moderated the relationship between social networks, flourishing only among widows but not widowers. Widows with low levels of extrinsic religiosity should join activities or programs that could expand their social networks to promote higher well-being despite widowhood.